¿How to design a business plan with success? - Vargas García, Allan (2018)
The business plan is a tool that guides the achievement of objectives through the development of strategies and plans, establishes the activities in an integral manner and establishes the bases for a business to be profitable. A business plan is applicable for start-up companies, projects that are just starting or business ideas. It should be used to develop new lines of products or services, renegotiate with suppliers or financial institutions, as well as to present it to new investors interested in maximizing their profitability.The proposed for “Designing a Successful Business Plan” is based on Steve Blank’s client development methodology, the business model generation of Alexander Osterwalder’s, and the methodology of traditional business development, to give rise to a new theory. With this new proposal you will be better prepared to overcome the uncertainty, but above all to take advantage of the opportunities, minimize risks and generate the profitability expected by the shareholders.